On The Exchange of Hostility With Supervisors: An Examination of Self‐Enhancing and Self‐Defeating Perspectives. Issue 4 (30th January 2015) - Tepper, Bennett J.; Mitchell, Marie S.; Haggard, Dana L.; Kwan, Ho Kwong; Park, Hee‐man
Abstract : We invoke competing theoretical perspectives to examine the consequences for subordinates of involvement in relationships that vary in terms of downward hostility (i.e., hostility enacted by supervisors against direct reports) and upward hostility (i.e., hostility enacted by subordinates against immediate supervisors). Consistent with the perspective that targets of downward hostility are less likely to see themselves as victims when they perform acts of upward hostility, analysis of 2‐wave data from a sample of supervised employees suggested that upward hostility weakens the deleterious effects of downward hostility on subordinates' job satisfaction, affective commitment, and psychological distress. Study 2 directly examined the presumed mechanism that underlies the effects observed in Study 1. In a 3‐wave sample, support was found for a moderated‐indirect effect framework in which the indirect effects of downward hostility on subordinates' attitudes and psychological distress (through victim identity) were weaker when upward hostility was higher. Study 2 results also suggested that the enhancing effect of upward hostility generalizes to subjective indicators of career satisfaction and future career expectations.